Impact of Zoning Changes on Property Values in West Sulawesi: A Difference-in-Differences Analysis - Ningsih, Selly Kudrati; Djannatin, Evatiwery; Hikmawati, Hikmawati (JAMPE (Journal of Asset Management and Public Economy), 2025)
This study explores how zoning regulations affect property values in West Sulawesi to understand the impact of zoning changes on real estate markets. The objectives include identifying the relationship between zoning modifications and fluctuations in property values and comparing areas that undergo zoning changes with those that do not. The study uses a quantitative research design and conducts a Difference-in-Differences analysis using secondary data from local property transactions, zoning maps, and demographic statistics from 2013 to 2023. The sample encompasses 150 neighborhoods throughout the province, offering a thorough perspective on local market dynamics. The results indicate a statistically significant positive correlation between zoning changes and rising property values, implying that updated regulations can effectively boost real estate market performance. The study also accounts for external factors, such as infrastructure development and local economic conditions, which significantly influence the outcomes of zoning changes. This research adds to the existing urban planning and property economics literature by demonstrating how zoning regulations can stimulate local economies and guide policy decisions. A key contribution of this study is its comparative analysis of property value changes in areas with and without zoning updates, providing valuable insights into the influence of zoning on property values in developing regions while emphasizing the importance of a holistic approach in assessing zoning impacts.